Infrahepatic ! caudal/inferior vena cava interruption with azygos/hemiazygos continuation. Vascular anomaly in swine - Jeromel, Miran (Radiology and oncology (Ljubljana), 2010)
Background. Electrochemotherapy is a local treatment combining application of electric pulses and chemotherapy. Two chemotherapeutic drugs, bleomycin and cisplatin, have proved to be effective in electrochemotherapy. The effectiveness of electrochemotherapy was demonstrated in the treatment of various cutaneous and subcutaneous tumours in cancer patients. Only a few preclinical studies were performed in colorectal carcinoma, mostly using bleomycin. Our aim was to evaluate the sensitivity of the murine colorectal carcinoma cell line CMT-93 to electrochemotherapy with bleomycin and cisplatinfor potential use in preclinical and clinical studies. Methods. CMT-93 cells were exposed to either the chemotherapeutic drug alone or electrochemotherapy. A clonogenic assay was used to determine cell survival after treatment. Apoptosis was measured by caspase-3/7 activity, necrosis by changes in cell morphology and cell viability by the MTS assay 16 hours after electrochemotherapy. Results. Cells treated with electrochemotherapy were 500-fold more sensitive to bleomycin and 2.8-fold more sensitive to cisplatin compared to cells treated with the drugs alone. At the highest concentrations,a significant reduction in cell viability, increase in caspase-3/7 activity and necrotic cells were observed after electrochemotherapy. Conclusions. Exposure of cells to electric pulses enhanced cytotoxicity of both bleomycin and cisplatin. Reduced cell viability was due to apoptotic and necrotic cell death. Furthermore, electrochemotherapywith bleomycin was more cytotoxic than electrochemotherapy with cisplatin in this colorectal carcinoma cell line.
Keywords: Abnormalities; Acigos, vena; Azygos Vein; Bolezen, živalski modeli; cardiovascular disease; Disease Models, Animal; Flebografija; kardiovaskularne bolezni; napake; Phlebography; Prašiči; Swine; Vena Cava, Inferior; Vena kava inferior; vene